The obesity paradox revisited: the body composition of myocardial infarction patients. (3rd May 2023) - Croissant, Y; Costa, D; Tapia, K; Barbosa, M B; Acosta, M F; Muzzio, M; Gregorietti, V; Coronel, R
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Obesity is a cardiovascular risk factor, but several studies have shown the protective effects of higher body mass index (BMI) in myocardial infarction (MI) patients. This phenomenon is denominated "obesity paradox", that is, there is a lower incidence of events in obese patients after an acute episode. However, we must not forget that the BMI has several limitations for classifying obesity. The aim of our study was to evaluate the associations of obesity and fat mass percentage measured by bioimpedance analysis (BIA) with events in patients with MI and treated with PCI. Methods: Observational study in patients admitted to a CCU for MI and treated with PCI. Body composition was assessed with tetrapolar BIA obtained at 50 kHz. Obesity was defined as a BMI greater than 30 kg/m2 and increased fat mass as a fat percentage greater than 25% in men and 35% in women. Major adverse cardiovascular events (MACE) during hospitalization were defined as type IV infarction (Third Universal Definition), heart failure, stroke, or death. Results: A total of 94 patients were included. The median age was 58 years (IQR 53 – 63), and 89% were male. Most of them presented with STEMI (53%), 32% had hypertension, 23% had diabetes, and the median creatinine on admission was 0.9 mg/dl (IQR 0.75 – 1.05). Body measurement showed that 30 (31.9%) had normal weight and fat mass, 30 (31.9%) had obesity and increased fat mass, 26 (27.7%) had normal weight and increased fat, and 8 (8.5%) had obesity with normal fat mass. There was a positive and significant correlation between BMI and fat mass (figure 1). A total of 31 patients (33.3%) had a MACE during hospitalization. Patients with MACE had lower BMI than patients that did not suffer MACE (28.31 ± 4.42 kg/m2 versus 30.57 ± 7.01 kg/m2, p = 0.04). On the other hand, fat mass was similar between patients with and without MACE (27.23 ± 6.19% versus 28.19 ± 8.01%, p = 0.53). Obese patients had a lower incidence of MACE than patients with a normal weight (21.1% versus 41.8%, p = 0.037), but there was no significant difference when comparing patients according to fat mass. Conclusion: Although the occurrence of MACE in the short term after a MI was associated with lower BMI, this was not determined by a lesser amount of body fat. This adds to the evidence that the obesity paradox is not related to fat mass but is probably generated by the shortcomings of the BMI as a surrogate for body composition. Correlation between BMI and fat mass.